Community mental health team case-loads and diagnostic case-mix - Greenwood, N; Chisholm, B; Burns, T; Harvey, K (2000)
Aims and method: Information concerning team staffing, keyworker case-loads, and keyworker diagnostic case-mix was collected from six community mental health teams caring for 1651 patients to establish the clinical burden across teams and professions. Results: Team case-loads varied from 427 to 121, an average of 275 patients. Over half the patients were female, and psychotic disorder constituted 44% of the sample. The most common diagnoses were schizophrenia (28.6%) and depression (23.6%). Keyworker case-loads varied across both teams and professions, averaging 30 patients per full-time equivalent. Psychiatrists' case-loads were the largest. Diagnostic case-mix varied with profession. Community psychiatric nurses had the largest proportion of patients with psychosis (73.8%). Clinical implications: Multi-disciplinary community mental health teams have a shared view of appropriate work distribution. Consultant psychiatrists may underestimate the resources required by patients with non-psychotic disorders even in inner city areas.